Characterization of Micromonospora spp. with Activity Against E.coli ATCC 35218 Resistance β-Lactam Antibiotics - DYAH NOOR HIDAYATI; YULIN LESTARI; BAMBANG MARWOTO (Indonesian Society for microbiology, 2013)
The emerge of antibiotic resistance has been an important issue all over the world, on the other hand, infectious diseases have been one of the highest causes of death causes in the world. Therefore, the discovery of a new antimicrobial drug is very important, and the group of rare actinomycetes are really promising as the producer of new bioactive compounds, in this case antibiotics. In this study we screened and characterized the actinomycetes with antibacterial activity against Escherichia coli ATCC 35218 resistant beta-lactam antibiotics. A total of 96 strains collected in Biotechnology Microbial Culture Collection (BioMCC), BPPT, were screened for their antibacterial activities by the agar plug method. Three strains, at-HH-64, at-HH-78, and at-HH-259, showed antibacterial activity. The selected strains were cultured on four different media, both solid and liquid media, e.g. ISP2, ISP4, Micromonospora Starch Medium (MS), and Bennet’s Medium (BM), and we characterized their morphology and growth patterns. Morphological characterization showed that all strains belonged to the genera Micromonospora. The active strains were also identified based on 16S rRNA partial sequence. BLAST search of the 16S rRNA sequences of all tested strains with the sequences available in the NCBI data bank showed a maximum similarity 99% with Micromonospora chersina.